2019
DOI: 10.1080/10428194.2019.1633632
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab biosimilar RTXM83 versus reference rituximab in combination with CHOP as first-line treatment for diffuse large B-cell lymphoma: a randomized, double-blind study

Abstract: & on behalf of the RTXM83 study (2019) Rituximab biosimilar RTXM83 versus reference rituximab in combination with CHOP as first-line treatment for diffuse large B-cell lymphoma: a randomized, double-blind study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…RTXM83 is approved in Argentina as a rituximab biosimilar. Published data are available for analytical and preclinical testing, as well as from a Phase III clinical trial in DLBCL [79][80][81]. Preclinical comparisons for RTXM83 and reference rituximab confirmed matching primary and higher-order structures, and post-translational modifications.…”
Section: Rituximab Biosimilars In Developmentmentioning
confidence: 91%
See 1 more Smart Citation
“…RTXM83 is approved in Argentina as a rituximab biosimilar. Published data are available for analytical and preclinical testing, as well as from a Phase III clinical trial in DLBCL [79][80][81]. Preclinical comparisons for RTXM83 and reference rituximab confirmed matching primary and higher-order structures, and post-translational modifications.…”
Section: Rituximab Biosimilars In Developmentmentioning
confidence: 91%
“…Overall, preclinical data showed that RTXM83 and reference rituximab are highly similar in terms of structure and function. In a Phase III confirmatory trial in DLBCL, the primary endpoint of noninferiority in ORR between RTXM83 and reference rituximab was met [81]. PK/PD profiles were also shown to be similar between the two treatment arms.…”
Section: Rituximab Biosimilars In Developmentmentioning
confidence: 99%
“…mAbxience (RTXM83) chose patients with this indication (DLBCL) as the most sensitive population, that exhibits good clinical responses to RTX in combination with cyclophosphamide, doxorubicin, vincristine and prednisone. Despite the challenging of recruiting, it was the first completed biosimilar comparability study in this patient setting despite the challenging of recruiting [56]. Later, HLX01, the candidate of Henlius was evaluated in the same population [54].…”
Section: Pharmacological Assessment Of Biosimilarity: Pk and Pd Comparative Studiesmentioning
confidence: 99%
“…Most developers such as Amgen, Boehringer Ingelheim, Mylan and Sandoz, performed two-sided equivalence trials to demonstrate similar clinical efficacy and safety to the RMP. In contrast, the RTX candidates RTXM83 (mAbxience) and Zytux TM (AryoGen Pharmed) were evaluated in a noninferiority trial [56,57]. The BEV candidate of Biocad (BCD-021) was also tested in a noninferiority trial [42].…”
Section: Pharmacological Assessment Of Biosimilarity: Pk and Pd Comparative Studiesmentioning
confidence: 99%
“…Other rituximab biosimilars have been developed (eg, MK-8808, BI 695500), but the manufacturers have since terminated development and are no longer listing the rituximab biosimilars as part of their product pipeline. 56-59…”
Section: Rituximab Biosimilar Use In Non-hodgkin Lymphomamentioning
confidence: 99%